Pengaruh Efektifitas Daya Hisap di LTDS 1 dan LTDS 2 terhadap Lossis Kernel Menggunakan Metode Gravimetri - Dion Saputra H; Rensus A. Pardede; Dea A. Persada Sinaga; Jusra Tampubolon; Jufri Antoni (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study was conducted to analyze the effect of suction power effectiveness on cyclones in Light Tenera Dust Separator (LTDS) 1 and 2 units on the level of palm kernel losses at PTPN IV Regional II Plantation Unit and Adolina Palm Oil Mill (POM). Palm kernel loss is a significant factor that can reduce production efficiency, as palm kernel has high economic value and is the main product in the palm oil industry. Kernel losses not only reduce production efficiency but also create significant economic disadvantages for the palm oil mill. The research method used was a gravimetric method with a field experiment approach. The research process included sampling from LTDS waste, separating kernels from shells, and measuring suction speed using an anemometer to determine cyclone performance. The gravimetric method was applied to quantify the proportion of kernel mixed with shell waste, providing measurable data on suction efficiency. The results showed that low suction power effectiveness was directly proportional to the increasing number of kernels that were thrown away with the shells. In other words, poor suction performance directly correlates with higher kernel losses. The main contributing factors include leaks in the cyclone, suboptimal blower settings, and inadequate operator skills. Operational skills and equipment maintenance were identified as crucial determinants of system performance. Based on these findings, improvements to the suction system are recommended through routine maintenance, leak checks, and blower setting calibration. Furthermore, operator training is required to precisely adjust suction power. By maintaining suction effectiveness and optimizing blower settings, kernel losses can be reduced below the standard threshold of 2.0%. Thus, mills can improve operational efficiency while minimizing economic losses due to palm kernel loss.